Genetic distributions of 22 short tandem repeat loci in 760 unrelated tibet, Uygur, and mongolia individuals from China - Ya-Ran Yang; Jian Yang; Feng Li; Yong-Zai Wang; Zai-Liang Yu; Jiang-Wei Yan; Di Lu (Wolters Kluwer Medknow Publications, 2019)
In recent years, paternity testing in ethnic minority areas in China increases rapidly. However, the number of existing genetic markers does not meet the needs. The objective is to study the information of 22 genetic markers in Mongolian, Tibetan, and Uygur Nationality. The genetic polymorphism of 22 short tandem repeat (STR) loci (D10S1435, D11S2368, D12S391, D13S325, D14S608, D15S659, D16S539, D17S1290, D18S535, D19S253, D1S1656, D20S470, D21S1270, D22GATA198B05, D2S1338, D3S3045, D4S2366, D5S2500, D6S477, D7S3048, D8S1132, and D9S925) was estimated in 259 Uyghur, 251 Tibetan, and 250 Inner Mongolian individuals from China who were all unrelated. Allele frequencies and forensic parameters were evaluated. The Hardy-Weinberg equilibrium (HWE) of each locus and the linkage disequilibrium (LD) for all pairwise STR loci were tested. Additionally, the Nei's genetic distance was used to estimate the genetic heterogeneity between Tibetan, Uyghur, Mongolian, Chinese Northern Han and Chinese Li population. The 22 loci showed high genetic polymorphism in the three ethnic groups. An exact test for the genotype distribution of the markers showed no significant deviation from HWE. These 22 STR loci could be treated as independent loci at the population level in these three ethnic groups. Relatively short genetic distances were found between the Mongolian and Han and Uygur populations. The 22 loci had no LD in the three ethnic groups and showed high heterozygosity, providing genetic information and forensic statistics for the Uyghur, Tibetan, and Inner Mongolian groups. These 22 STR loci will be useful for identification and kinship analysis in these three populations in China.